C++ programming - Li, Zheng; Dong, Yuan; Yang, Fang (Walter de Gruyter ; Tsinghua University Press, 2019)
This book begins by explaining key concepts in programming, and elaborates on characteristic of class, including inheritance, derivation and polymorphism. It also introduces generic programming and Standard Template Library, I/O Stream Library and Exception Handling. The concepts and methods are illustrated via examples step by step, making the book an essential reading for beginners to C++ programming.- Resumé vydavatel
Includes index.
Keywords: C++ (programovací jazyk); programování; C++ (programming language); programming; elektronické knihy; učebnice vysokých škol; electronic books; textbooks (higher)